Processo do aleitamento materno em lactentes portadores de fatores de risco para o desenvolvimento - Pedreira, Vely Ferreira (2014)
Breastfeeding (BF) is subject of studies and scientific researches worldwide. It s known that it brings benefits in short, medium and long-terms to premature and full term infants, to mothers, and to society in general. Since the 70s, governmental and non-governmental organizations have been developing and implementing trategies in order to contribute the increase in quality and duration of breastfeeding. However, despite scientific evidence and commitment from various segments, results haven t reached desired rates. Exclusive breastfeeding up to six months old infants and with complements up to 2 years old is far from reality for all children. This scenario is even worse when there are risk factors for development in newborn s history. In such cases, the need for intervention becomes a priority by professionals, family and particularly the mother, and the process of breastfeeding is often not focused. In this context, this study aims to investigate breastfeeding process for infants with development risk factors. The sample comprised 30 mothers of infants who presented development risk factors, aged 6 months to 1 year from both genres. They are attended by the Early Stimulation Program at Apae Bauru s Rehabilitation Center. All participants answered a questionnaire consisting of infant s identification data and questions about family history, obstetric, pregnancy, and issues related to breastfeeding. Results showed that 66.7% of mothers and 70.0% of fathers were adults in reproductive age; the risk factor of highest incidence was prematurity (56.66%); 53.3% of neonates remained hospitalized at neonatal intensive-care units and / or in nurseries, after the mother s discharge, from 2 to 50 days, 40.0% of infants used a nasogastric tube from 3 to 37 days. All mothers received information about breast feeding, and 96.7% were informed during prenatal, and 90.0% of received information in puerperium; practical nurses were the professionals who gave mothers information in most cases and it was given them individually 86.7%; all participants reported difficulties in breastfeeding process and introduced complementary food in the first month; 46.6% of participants could not breastfeed, and only 16.6% of them breastfed for more than 6 months; 40.0% demanded help from a milk bank. No relationship was found between duration of breastfeeding and demand for milk bank and also duration of breastfeeding and use of pacifiers. This reality points to a need for greater involvement of health professionals. Especially those operating in prenatal and puerperium should advocate strategies for breastfeeding promotion on their actions